An introduction to the mechanics of solids in si units [3rd ed.] - Archer, Robert R.; Cook, Nathan H.; Crandall, Stephen H.; Dahl, Norman C. (New Delhi Mcgraw Hill Education, 2012)
This text is based on the understanding and application of three fundamental physical considerations which govern the mechanics of solids in equilibrium. All the discussion and theoretical development is explicitly related to these three basic considerations. This approach brings in unity to an elementary presentation of the subject. Considerable emphasis has been put on the process of constructing idealized models to represent actual physical situations.
Keywords: Mechanics, Applied; Solids; Strength of materials